Combined Influence of Fly Ash and Recycled Coarse Aggregates on Strength and Economic Performance of Concrete - Babar Ali; Liaqat Ali Qureshi; Muhammad Asad Nawaz; Hafiz Muhammad Usman Aslam (Salehan Institute of Higher Education, 2019)
Recycled coarse aggregates (RCA) and fly ash (FA) are materials with least to very low global warming potential. Considering long term strength and durability, various studies have suggested to use RCA in concrete with FA. This research paper deals with the strength and economic performance of concrete made with individual and combined incorporation of FA and RCA. Nine different mixtures of concrete were prepared by varying the incorporation levels of RCA and FA. 0% RCA, 50% RCA and 100% RCA were used in concrete with three different levels of FA (0%FA, 20%FA, and 40%FA). The compressive strength of each mixture of concrete was determined at the age of 3, 28, 90 and 180 days. To evaluate economic performance cost of 1 m3 of each mixture of concrete was compared to that of the control mixture having 0% RCA and 0% FA. Results showed that RCA was detrimental to the compressive strength of concrete at all ages, whereas, FA reduced early strength but improved the strength at later ages of testing i.e. 90 and 180 days. FA plus RCA mixes also showed lower early age strength but gained higher strength than conventional concrete at the age of 180 days. RCA did not reduce the cost of concrete effectively. FA despite having a very high transportation cost, it reduced the cost of concrete efficiently. FA did not only reduce the cost of binder but also lower the demand of plasticizer by improving workability. Cost to strength ratio (CSR) analysis also indicated that FA significantly improve the combined economic and strength performance of RCA concrete mixes.